Internationalisation as a boost for many firms: evidence from Germany - Rainer Frey; Stefan Goldbach (Review of World Economics, 2024)
The advantages of globalisation have been increasingly called into question, and protectionist tendencies have entered the stage. So what experiences have firms had after going international in an open economy over the past years? With respect to foreign investor takeovers of initially national firms, we see predominantly positive effects for acquired manufacturing firms in terms of productivity, sales and expenditures on the labour force – likely due to higher employment – in the short and long term. Looking at the results, firm size matters: positive effects are stronger among large firms. In the case of firms starting to invest abroad, positive effects are very rare and limited to short-term sales of acquiring small manufacturing firms. All in all, the largely positive evidence is generally supportive of internationalisation and thus largely contradicts the negative views sometimes present in the public sphere, though even unaffected firms may see themselves as relative losers.
Keywords: D22; D24; F23; G34; 330; Globalisation; Firm acquisition; M&A; Productivity; Sales; Intangible assets; Knowledge; Technology; Labour costs; Employment; Wages; Firm heterogeneity